2013
DOI: 10.1016/j.physleta.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantum equivalence principle without mass superselection

Abstract: The standard argument for the validity of Einstein's equivalence principle in a non-relativistic quantum context involves the application of a mass superselection rule. It is surprising that the consistency between such an important principle and quantum mechanics depends crucially on the imposition of a non-fundamental restriction. The objective of this work is show that, contrary to what the standard account holds, the compatibility between the principle of equivalence and quantum mechanics does not depend o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The framework devised by Bargmann constrains the compatibility of quantum mechanics with both GC and EEP to the nonexistence of mass superpositions. While Bargmann's formal construction is widely accepted in the literature and already figures as textbook content [2,3], his conclusion has been recurrently debated [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In particular, some authors interpreted the massdependent phase as a residue of the twin-paradox effect in nonrelativistic quantum mechanics [4,17], thus attributing deeper physical meaning to it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework devised by Bargmann constrains the compatibility of quantum mechanics with both GC and EEP to the nonexistence of mass superpositions. While Bargmann's formal construction is widely accepted in the literature and already figures as textbook content [2,3], his conclusion has been recurrently debated [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In particular, some authors interpreted the massdependent phase as a residue of the twin-paradox effect in nonrelativistic quantum mechanics [4,17], thus attributing deeper physical meaning to it.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are some works defending that quantum mechanics is compatible with EEP [18][19][20]. In consonance with a program initiated long ago [7][8][9][10], it was recently suggested that the mass-superselection rule can be avoided if mass is taken as a dynamical variable [5]. Regardless of their conclusions, all of the aforementioned works stick to traditional ingredients, namely, the reference frames are fundamentally classical and the analysis is focused on the wave function.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, proposals were put forward to simulate dynamics of mass-superpositions with quantum optical setups in order to test MSR experimentally [6]. On the other hand a fully consistent formalism has been developed where mass and proper time are conjugate dynamical variables [7][8][9][10][11]. This challenges the above approaches and shows that neither physical meaning nor validity of MSR are fully understood.…”
mentioning
confidence: 99%
“…( 7)). We usually do not think of time dilation effects as demonstrating masssuperpositions -nor as effects violating MSR -although H le with H r → M c 2 is operationally the same as H dm , with the added rest mass term, as in refs [7][8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation